2012
DOI: 10.1021/jf301917q
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Galaxolide, Tonalide, and Triclosan by Carrot, Barley, and Meadow Fescue Plants

Abstract: Many xenobiotics entering wastewater treatment plants are known to be persistent during wastewater treatment and tend to adsorb to sewage sludge. The application of sewage sludge as fertilizer in agriculture may pose the risk of an incorporation of xenobiotics in the cultivated plants and, finally, an inclusion into the food chain. This study was performed to investigate the uptake of common sewage sludge contaminants, galaxolide, tonalide, and triclosan, by plants used for human consumption and livestock feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…The poor bioaccumulation capacity of the polycyclic musks in leaf was observed in previous studies. The only work reported by Macherius et al showed that the BCFs in carrot leaf grown in spiked soil were 0.76 and 0.18 for HHCB and AHTN (Macherius et al, 2012), respectively, which generally agrees with the results in this study. However, the environmental fates of nitro musks in plants have not been reported.…”
Section: Uptake Elimination and Translocation Of Sms In Aloesupporting
confidence: 93%
“…The poor bioaccumulation capacity of the polycyclic musks in leaf was observed in previous studies. The only work reported by Macherius et al showed that the BCFs in carrot leaf grown in spiked soil were 0.76 and 0.18 for HHCB and AHTN (Macherius et al, 2012), respectively, which generally agrees with the results in this study. However, the environmental fates of nitro musks in plants have not been reported.…”
Section: Uptake Elimination and Translocation Of Sms In Aloesupporting
confidence: 93%
“…Currently, the QuEChERS method has been extended to determine pharmaceuticals in eggs, meats, fish and sewage sludge [25,32,33]; however, few studies were conducted to quantify pharmaceuticals in vegetables and crop produce using the QuECh-ERS method [34]. Salvia et al [35] showed that both ASE and a modified QuEChERS method could effectively extract multiple classes of pharmaceuticals from soils.…”
Section: Introductionmentioning
confidence: 99%
“…These sludges are typically used as substrates in anaerobic reactors. Additionally, many of these micropollutants are used in the livestock industry and through the animal slurry they end up in the manurebased anaerobic reactors [9,10]. The adverse impacts of all the micropollutants on the manure-based AD reactors are not clear yet.…”
Section: Introductionmentioning
confidence: 99%